Population specific impact of genetic variants in KCNJ11 gene to type 2 diabetes: a case-control and meta-analysis study. - Nagaraja M Phani; Vasudeva Guddattu; Ravishankara Bellampalli; Venu Seenappa; Prabha Adhikari; Shivashankara K Nagri; Sydney C D Souza; Gopinath P Mundyat; Kapaettu Satyamoorthy; Padmalatha S Rai (PLoS ONE)
Background and objectives Potassium inwardly rectifying channel, subfamily J, member 11 (KCNJ11) gene have a key role in insulin secretion and is of substantial interest as a candidate gene for type 2 diabetes (T2D). The current work was performed to delineate the genetic influence of KCNJ11 polymorphisms on risk of T2D in South Indian population through case-control association study along with systematic review and meta-analysis. Methods A case-control study of 400 T2D cases and controls of South Indian origin were performed to analyze the association of KCNJ11 polymorphisms (rs5219, rs5215, rs41282930, rs1800467) and copy number variations (CNV) on the risk of T2D. In addition a systematic review and meta-analysis for KCNJ11 rs5219 was conducted in 3,831 cases and 3,543 controls from 5 published reports from South-Asian population by searching various databases. Odds ratio with 95% confidence interval (CI) was used to assess the association strength. Cochran's Q, I2 statistics were used to study heterogeneity between the eligible studies. Results KCNJ11 rs5215, C-G-C-C haplotype and two loci analysis (rs5219 vs rs1800467) showed a significant association with T2D but CNV analysis did not show significant variation between T2D cases and control subjects. Lower age of disease onset (P = 0.04) and higher body mass index (BMI) (P = 0.04) were associated with rs5219 TT genotype in T2D patients. The meta-analysis of KCNJ11 rs5219 on South Asian population showed no association on susceptibility to T2D with an overall pooled OR = 0.98, 95% CI = 0.83-1.16. Stratification analysis showed East Asian population and global population were associated with T2D when compared to South Asians. Conclusion KCNJ11 rs5219 is not independently associated with T2D in South-Indian population and our meta-analysis suggests that KCNJ11 polymorphism (rs5219) is associated with risk of T2D in East Asian population and global population but this outcome could not be replicated in South Asian sub groups.